2006
DOI: 10.1523/jneurosci.3707-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Cell Cycle Events Link Human Alzheimer's Disease and Amyloid Precursor Protein Transgenic Mouse Models

Abstract: Nerve cells that re-enter a cell cycle will die rather than divide, a fact that likely underlies the neurodegeneration in Alzheimer's disease (AD). Several mouse models of familial AD have been created, and although many display amyloid plaques in their brains, none captures the extensive pattern of nerve cell death found in the human disease. Using both immunocytochemistry and fluorescent in situ hybridization, we show that neurons in three different mouse models reproduce the ectopic cell cycling found in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
144
4

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 49 publications
(55 reference statements)
12
144
4
Order By: Relevance
“…However, aberrant entry into the cell cycle has been reported to precede neuronal death in the cortex and CA3 regions at all stages of AD, from MCI to late stage AD and within AD mouse models (34). Further, expression of the ectopic cell-cycle proteins ultimately predicts the demise of these neurons (35). These findings are especially challenging for therapeutics targeting the regenerative potential of endogenous neural stem/progenitor populations, as an unintended side effect may be to promote ectopic entry of neurons into the cell cycle and thereby exacerbate neuron demise.…”
Section: Discussionmentioning
confidence: 99%
“…However, aberrant entry into the cell cycle has been reported to precede neuronal death in the cortex and CA3 regions at all stages of AD, from MCI to late stage AD and within AD mouse models (34). Further, expression of the ectopic cell-cycle proteins ultimately predicts the demise of these neurons (35). These findings are especially challenging for therapeutics targeting the regenerative potential of endogenous neural stem/progenitor populations, as an unintended side effect may be to promote ectopic entry of neurons into the cell cycle and thereby exacerbate neuron demise.…”
Section: Discussionmentioning
confidence: 99%
“…The abortive cell cycle re-entry has been reported in the brain of patients and in most AD animal models, 24,35,36 as well as in cultured neurons exposed to Aβ peptides. 23,35 Interestingly, in several pathologies in which ectopic cell cycle events have been described, Cdk5 overactivation also occurs.…”
Section: Discussionmentioning
confidence: 97%
“…Tau hyperphosphorylation was shown to be correlated with Cdk5 overactivation in experimental models of AD and PRE. 6,38 Recently it was reported that re-expression of cell cycle proteins in AD patients can occur prior to tau hyperphosphorylation, 11,36 and that cell cycle activation may contribute to the formation of NFTs, 39 which may be a sign of possible interconnection between both events. Moreover, some studies have also shown that abnormal tau phosphorylation precedes neuronal apoptotic death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taumediated neurodegeneration in this area is thought to play a role in Alzheimer disease progression (Shahani N et al, 2006). Recent evidence is mounting in support of an alternative hypothesis for Alzheimer disease pathology, which implicates cell cycle reactivation as a key early event that precedes and possibly is causally related to tau, APP phosphorylation and apoptotic cell death (Andorfer C et al, 2005;McPhie DL et al, 2003;Yang Y et al, 2006). Amyloid precursor protein has been purported to regulate activation of neuronal cell cycle proteins (McPhie DL et al, 2003); therefore, hypothetically, mutations in VR22 could indirectly affect cell cycle activation, through interactions with APP (by way of beta-catenin and presenilin 1).…”
Section: Discussionmentioning
confidence: 99%